Safety and effectiveness of very high-power short duration ablation in patients with atrial fibrillation: early results. (3rd October 2022) - Mitrzak, K; Krzowski, B; Peller, M; Maciejewski, C; Marchel, M; Balsam, P; Grabowski, M; Lodzinski, P
Abstract: Background: Pulmonary vein isolation (PVI) is at the forefront of treatment methods of rhythm control in patients with atrial fibrillation (AF) (1). The novel contact-force sensing catheter, QDot MicroTM (Biosense Webster) was designed to improve effectiveness of AF ablation and allow better time management due to shorter procedure time. It is a very high power-short duration (vHP-SD) catheter optimized for high density mapping and temperature control, which enables the application of high energy (up to 90W, 4s) (2). Purpose: The aim of the study was to compare the QDot MicroTM catheter with the ThermoCool SmarttouchTM SF catheter with regard to the effectiveness and safety of PVI ablation. Methods: It is a single center, cross-sectional, observational study enrolling 101 consecutive patients suffering from symptomatic paroxysmal or persistent AF, referred for first catheter ablation between 16 December 2019 and 03 December 2021. In 47 procedures (mean age 54 years; 70% male; 77% paroxysmal) the QDot Micro catheter was used (vHP-SD group; Qmode+ 90W, 4s), whereas the remaining 54 patients (mean age 57 years; 70% male; 67% paroxysmal) were treated with the ThermoCool SmarttouchTM SF catheter (control group, Ablation Index guided ablation). The primary endpoint was freedom from AF at 3-months after ablation. The secondary endpoints included the amount of opioids administered as well as the incidence of early-onset treatment-emergent adverse events (TEAEs). Results: AF recurrence was documented in 14.9% patients in vHP-SD group and in 31.5% patients in control group (p=0.06). The mean dose of remifentanil was reported to be lower during Qmode+ catheter-based PVI (0.50 (0.40–0.60) vs. 0.70 (0.55–0.90) mg; p<0.001). There was no statistically significant difference in TEAEs between both groups (6.3 vs. 0%; p=0.10). One severe adverse event (cerebral vascular incident 2 days after PVI – due to thrombus in the left ventricle) was observed in vHP-SD group. Conclusions: This study suggests that the vHP-SD ablation is safe and enables sedative-analgesic medications demand reduction during procedure. vHP-SD mode may enhance the success rate of catheter-based PVI, however further research is needed to provide additional evidence of its superiority. Funding Acknowledgement: Type of funding sources: None.